Modern Diagnostic Methods and Pathomechanisms of Eosinophilic Esophagitis – A Review - Szamocka, Karolina; Strzewiczek, Aleksandra (Quality in Sport, 2026)
Introduction. Eosinophilic esophagitis (EoE) is a chronic immune-mediated disease characterized by eosinophil-predominant inflammation of the esophageal mucosa. Over the last two decades, the incidence and prevalence of EoE have increased significantly, making it one of the most important causes of dysphagia and food impaction in children and adults. The disease results from complex interactions between genetic predisposition, environmental factors, and immune system dysregulation, particularly involving Th2-mediated inflammatory pathways. Aim of the Study. The aim of this review is to summarize current knowledge regarding the pathomechanisms underlying eosinophilic esophagitis and to analyze modern diagnostic methods used in clinical practice and research. Particular emphasis is placed on immunological mechanisms, molecular pathways, biomarkers, and emerging technologies that may improve early detection and disease monitoring. Materials and Methods. A literature review was conducted using major scientific databases including PubMed, Scopus, and Web of Science. Articles published between 2000 and 2025 were analyzed using keywords such as “eosinophilic esophagitis,” “pathophysiology,” “diagnostic methods,” “biomarkers,” and “immunology.” Only peer-reviewed studies and reviews focusing on molecular mechanisms, clinical diagnostics, and emerging technologies were included. Conclusion. Current evidence suggests that EoE is driven primarily by Th2 immune responses involving cytokines such as IL-4, IL-5, and IL-13, leading to eosinophil recruitment, epithelial barrier dysfunction, and progressive esophageal remodeling. Advances in diagnostic technologies, including molecular profiling, minimally invasive sampling, and artificial intelligence–assisted histology, are expected to significantly improve disease detection and personalized management.